Improving the Practice of Forensic Investigation of Buildings and Structures Undergoing Reconstruction - Andrei Yu. Butyrin; Igor’ A. Danilkin (Теория и практика судебной экспертизы)
The paper examines methodological problems associated with one of the types of examinations conducted by construction forensics experts. The objective of such examinations is to establish the variety, scope, and cost of construction work involved in the reconstruction of buildings and structures. Considering the courts' growing demand for this kind of investigations, on the one hand, and current inadequacy of supporting methodologies, on the other, the authors offer a detailed description and conclusive rationale for an optimal procedure for the epistemic actions designed to achieve one of the most commonly addressed forensic objectives.